A Putative Plasma Membrane Na+/H+ Antiporter GmSOS1 Is Critical for Salt Stress Tolerance in Glycine max - Zhang, Minghui; Cao, Junfeng; Zhang, Tianxu; Xu, Tao; Yang, Liyuan; Li, Xiaoyuan; Ji, Fengdan; Gao, Yingxue; Ali, Shahid; Zhang, Qingzhu; Zhu, Jianhua; Xie, Linan (Frontiers in Plant Science, 2022)
Soybean (Glycine max) is a staple crop and a major source of vegetable protein and vegetable oil. The growth of soybean is dramatically inhibited by salt stress, especially by the excessive toxic Na+. Salt Overly Sensitive 1 (SOS1) is the only extensively characterized Na+ efflux transporter in multiple plant species so far. However, the role of GmSOS1 in soybean salt stress responses remains unclear. Herein, we created three gmsos1 mutants using CRISPR-Cas9 system in soybean. We found a significant accumulation of Na+ in the roots of the gmsos1 mutants, resulting in the imbalance of Na+ and K+, which links to impaired Na+ efflux and increased K+ efflux in the roots of the gmsos1 mutants under salt stress. Compared to the wild type, our RNA-seq analysis revealed that the roots of the gmsos1-1 showed preferential up- and down-regulation of ion transporters under salt stress, supporting impaired stress detection or an inability to develop a comprehensive response to salinity in the gmsos1 mutants. Our findings indicate that the plasma membrane Na+/H+ exchanger GmSOS1 plays a critical role in soybean salt tolerance by maintaining Na+ homeostasis and provide evidence for molecular breeding to improve salt tolerance in soybean and other crops.